THE COMPETENCY MODEL FOR SURVEYOR COMPETENCY OF LARGE-SCALE IRRIGATION PROJECTS IN THE LAO PEOPLE’S DEMOCRATIC REPUBLIC (LAO PDR) - Sisouvanthong, Vorlachith; Kamkankaew, Pongsiri (Strategic Perspectives on Business and Marketing Management, 2022)
In the Lao People’s Democratic Republic (Lao PDR), human resource development is critical. In the Lao PDR, competence drives the growth of human capital, particularly in the construction of surveys for massive irrigation projects. Large-scale irrigation projects begin with surveyors contributing to design and construction monitoring. This research aims to create a core competency model for surveyors working on large-scale irrigation projects in Laos. The goal of content analysis is to synthesize qualitative research findings into a coherent whole. According to the findings, surveyors of large irrigation projects in the Lao People’s Democratic Republic have three complementary performance characteristics. These are knowledge characteristics, skill attributes, and personal traits. The outcomes of this research will aid in the development of human capital and improve irrigation surveying capabilities by utilizing human resources in the Lao People’s Democratic Republic’s exploration of large-scale irrigation projects (Lao PDR). The findings of this study can be used to improve the professional potential of irrigation surveyors in the Lao People’s Democratic Republic by planning operations in various domains and applying the body of knowledge in the classroom. Governments and related government agencies can also use the research results in the Lao People’s Democratic Republic to plan, educate, and develop surveyors’ capacity to perform successfully and efficiently. Further, survey participants’ organizations or agencies may use the data to improve explorers’ skills and expertise. It may allow the firm to find new potential in its personnel, allowing them to learn new skills and allowing the corporation to start new businesses that will benefit the company.